The Heroes of Olympus: The Son of Neptune - Book 2 - Riordan, Rick; Swanson, Joshua, 1978-; Stark, Janet; Sanders, Fred, 1955-; Listening Library (New York : Listening Library/Random House Audio, 2011)
After three demigods named Jason, Piper, and Leo visit Camp Half-Blood, they inherit a quest: to free Hera, a prisoner of Gaia. But who are the other four demigods mentioned in prophesy who will join them in their quest? The answer may lie in another camp miles away, where a new camper has shown up and appears to be the son of Neptune, god of the sea.
Keywords: Gaia (Greek deity) -- Juvenile fiction; Hera (Greek deity) -- Juvenile fiction; Neptune (Roman deity) -- Juvenile fiction; Camps -- Juvenile fiction; Mythology, Greek -- Juvenile fiction; Mythology, Roman -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Gaia (Greek deity) -- Fiction; Hera (Greek deity) -- Fiction; Neptune (Roman deity) -- Fiction; Camps -- Fiction; Mythology, Greek -- Fiction; Mythology, Roman -- Fiction; Quests (Expeditions) -- Fiction; Fantasy; Children's audiobooks